Modeling and simulation of an asymmetric plane diffuser - Siti Qhadijah, Abdul Rashid (2007)
This thesis deals with modeling and simulation of an asymmetric plane diffuser which is the most interesting test case in flow field by using Fluent software. The objective of this thesis are to understand the physical of the flow field in the plane diffuser, to evaluate turbulence model performance in predicting flow field using CFD commercial code, FLUENT and to compare with experimental data. The flow behavior includes pressure distribution and velocity profiles in asymmetric plane diffuser was investigated using three turbulence modeling which are realizable k-c model, standard k- co model and SST k- co model. The results from the simulation was compared to the experimental data (Buice & Eaton 1997) in order to produce accurate result. The acquired results of pressure distribution shows that both k- co model provide a fairly accurate in beginning stage while realizable k- c shows the worst result. For velocity profiles within the diffuser, the simulation results are much different from the experiment except the bottom half of the diffuser. The realizable k- c model being the worst followed by standard k- co model while SST k- co model gives better result. For the recirculation region, SST k- co model predicts the biggest region while realizable k-c model shows the smallest. The CFD commercial codes can solve problems faster and the best way to determined the fluid flow in this project.